A case study on developing a web-based contingency plan for business crises. (1st January 2001) - Lee, Young-Jai
A contingency plan for a public organisation was developed through vulnerability analysis, business area impact analysis, risk management and exercise, in terms of computer breakdowns, traffic accidents/explosions and facility crashes. The plan considers the organisation's procedures, tasks, report structure and resources. However, this paper-based plan is limited to use within the organisation. A more comprehensive web-based contingency plan therefore was built using intranet technology and a database, which include personal and physical resources. The database is also linked to other human resource management and document management databases. System users are easily able to access procedures and needed information through the network when they face business crises. Personal and physical resources are automatically updated via database links. Additionally, the web service programs offer crisis communication internally and externally through status reports and statistical data.